Redox Mechanisms in Cisplatin Resistance of Cancer Cells: The Twofold Role of Gamma-Glutamyltransferase 1 (GGT1) - Pompella, Alfonso; Corti, Alessandro; Visvikis, Athanase (Frontiers in Oncology, 2022)
Cisplatin (CDDP) is currently employed for the treatment of several solid tumors, but cellular heterogeneity and the onset of drug resistance dictate that suitable biomarkers of CDDP sensitivity are established. Studies on triple-negative breast cancer (TNBC) have recently confirmed the involvement of gamma-glutamyltransferase 1 (GGT1), whose enzyme activity expressed at the cell surface favors the cellular resupply of antioxidant glutathione (GSH) thus offering cancer cells protection against the prooxidant effects of CDDP. However, an additional well-established mechanism depends on GGT1-mediated matabolism of extracellular GSH. It was in fact shown that glycyl-cysteine – the dipeptide originated by GGT1-mediated GSH metabolism at the cell surface – can promptly form adducts with exogenous CDDP, thus hindering its access to the cell, interactions with DNA and overall cytotoxicity. Both mechanisms: mainainance of intracellular GSH levels plus extracellular CDDP detoxication are likely concurring to determine GGT1-dependent CDDP resistance.